Long island compromise ebook A novel. - Brodesser-Akner, Taffy (2024)
NATIONAL BESTSELLER • An exhilarating novel about one American family and the dark moment that shatters their suburban paradise, from the New York Times bestselling author of Fleishman Is in Trouble New York Times Book Review Editors’ Choice • New York Magazine’s Beach Read Book Club Pick • Belletrist Book Club Pick A BEST BOOK OF THE YEAR: The New York Times Book Review, Oprah Daily, The New Yorker, Time, The Washington Post, NPR, Vogue, Town & Country, New York Post, Harper’s Bazaar, Elle, Parade, Kirkus Reviews “Joins the pantheon of great American novels.”— Los Angeles Times “Exuberant and absorbing . . . a big old-fashioned social novel.”— The Atlantic “Were we gangsters? No. But did we know how to start a fire?” In 1980, a wealthy businessman named Carl Fletcher is kidnapped from his driveway, brutalized, and held for ransom. He is returned to his wife and kids less than a week later, only slightly the worse, and the family moves on with their lives, resuming their prized places in the saga of the American dream, comforted in the realization that though their money may have been what endangered them, it is also what assured them their safety. But now, nearly forty years later, it’s clear that perhaps nobody ever got over anything, after all. Carl has spent the ensuing years secretly seeking closure to the matter of his kidnapping, while his wife, Ruth, has spent her potential protecting her husband’s emotional health. Their three grown children aren’t doing much better: Nathan’s chronic fear won’t allow him to advance at his law firm; Beamer, a Hollywood screenwriter, will consume anything—substance, foodstuff, women—in order to numb his own perpetual terror; and Jenny has spent her life so bent on proving that she’s not a product of her family’s pathology that she has come to define it. As they hover at the delicate precipice of a different kind of survival, they learn that the family fortune has dwindled to just about nothing, and they must face desperate questions about how much their wealth has played a part in both their lives’ successes and failures. Long Island Compromise spans the entirety of one family’s history, winding through decades and generations, all the way to the outrageous present, and confronting the mainstays of American Jewish life: tradition, the pursuit of success, the terror of history, fear of the future, old wives’ tales, evil eyes, ambition, achievement, boredom, dybbuks, inheritance, pyramid schemes, right-wing capitalists, beta-blockers, psychics, and the mostly unspoken love and shared experience that unite a family forever.